Golygon - Ros, Manon Steffan (Y Lolfa, 2017)
Personal and piercing essays by Manon Steffan Ros, one of Wales' best contemporary authors. The essays, which deal with various topics such as People, Culture, Places and Suffering comprise comprise material which appeared originally in her weekly column in Golwg. Intro – CYFLWYNIAD – DIGWYDDIADAU – Trai Aberystwyth – MH370 Kuala Lumpur - Beijing – Cofio D-Day – Dydd Gwener Du – Charleston – Je Suis Charlie, Je Suis Ahmed – Calon Lân Llangefni – 30 Mlynedd ers colli'r Challenger – Brexit – Cymru v. Slofacia – POBOL – Gerallt – Calan Aberstalwm – Cofio T. Llew – Gwyn Thomas – Diolch, Gareth F. – Omran Daqneesh – Rhun ap Iorwerth ar Question Time – Corbyn – Pen-blwydd Dafydd Êl – Dagrau Carwyn – Neil Hamilton – Prifathro ysgol yn Rhuthun – William yn cefnogi Cymru – Delilah – Diolch, Gary – Diolch, Irfon – Diolch, Dafydd – Diolch, Rhodri – Trump, yr ymgeisydd – Buddugoliaeth Trump – 'Is there life on Mars?' – Llongyfarchiadau, Llion – EIN DIWYLLIANT – Rhagbrofion – Mistar Urdd – Dawns y Blodau – Gŵyl y Gelli – Y mwyafrif – Y Gadair – Maes B – Sioe'r pentref – Diolch – 9Bach – S4C – LLEOEDD – Neuadd Pantycelyn – Bywyd ym Mhantycelyn – Concyrs – Crufts – Ysgol Fomio Llanbedr – Traeth Gaza – Guerre Paris – Orlando – Senedd-dy Glyndŵr – Cofiwch… – Trychineb Dolgarrog – Tanchwa Gresffordd – Cyn-Brif Weinidog Japan ym Môn – Tân gwyllt Nice – Ysgol Gynradd Llangennech – Rio – DIODDEFAINT – Benefits Street – 90 oed – £369 miliwn ar Balas Buckingham – 8,000 o dai i Wynedd – Gwlâu gweigion – Brangelina – Dim colur – Haid – Rhyfel arall – Aber-fan – Hedfan awyren – Burkini – BYWYD YN EI AMRYWIAETH – Y pethau bychain – Cairns – Land Rover ar fynydd – Dur – Cenedlaetholdeb – Eithafiaeth – Gadael – Eginblanhigyn – Mwyar duon – Cynffonnau ŵyn bach – Dydd Sul arall – Gwres – Haul – Troi'r clociau – Cydsynio – Arholiadau – UKIP – Plant Mewn Angen – Mair - stori'r Geni – DYDDIADAU PWYSIG – Ffydd – Adfent – Gwyn – Hela'r dryw – Rhosynnau Dwynwen – Rhyddid ar ddydd Santes Dwynwen – Cyhydnos y gwanwyn – Grawys – Sul y Mamau.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books